Pengaruh Bauran Pemasaran Terhadap Keputusan Konsumen Membeli Produk Tenun Nazifah’s Collection Dusun Semberang 1 Kecamatan Sambas - Nurul Hidayah; Samsuddin Samsuddin; Dedi Hariyanto (Universitas Muhammadiyah Pontianak, 2018)
The objective of this research was to find out the influence of the marketing mix on consumer decisions in buying woven products Nazifah’s Collection Dusun Semberang 1 Kecamatan Sambas. The research method used in this research was descriptive method. The population in this study were consumers who buy woven products Nazifah’s Collection, with sample of 100 consumers.The results of the validity and reliability test showed that all item (statement) were valid and reliable. the results of the normality test showed that the data were normally distributed. The results of simple linear regression analysis showed the equation: Y = 1.036 + 0776X. The results of the correlation coefficient test showed that the R value is 0.631 it can be concluded that the marketing mix has a strong relationship with the decision to purchase woven products Nazifah’s Collection. The results of the coefficient of determination of the value of R 0.398 means that 3.98% of consumers' decisions to buy woven products are influenced by the marketing mix, while the rest (60.2%) was influenced by other variables not examined in this study. The results of the model feasibility test show that the calculated F value is 64.872> F table 3.94. It can be concluded that a simple linear regression model can be used to predict the purchase decisions of woven products Nazifah’s Collection that were influenced by the marketing mix.